n Voorligtinghulpverleningstrategie ten opsigte van skoolklimaat - Van Schalkwyk, O. T. v. N.(Ockert Tobias van Niekerk) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ed.) -- Universiteit van Stellenbosch, 1995.